Blueprint for Implementing and Improving Eligible Inferior Vena Cava (IVC) Filter Retrieval Across Institutions - Nygard, Adam; Hanna, Nicholas; Fiore, Gerre; Rohr, Aaron; Alli, Adam; Collins, Zachary; Irani, Neville (Kansas Journal of Medicine, 2022)
INTRODUCTION. Placement of removable filters (rIVCFs) has increased, but this has not been accompanied by timely removal, with retrieval rates as low as 8.5% at some institutions. Studies demonstrate failure to remove rIVCFs that are not medically necessary result in increased complications. This study discusses the development of an IVC filter follow up protocol.METHODS. A method to monitor IVC filter placement and retrieval was developed. A weekly report was generated detailing placement and removal of rIVCFs. A standardized retrieval calculator was utilized to determine efficacy of removal. An IVC filter Retrieval Assessment Form was developed. Managing physicians and patients with medically unnecessary filters were sent letters with a retrieval checklist and order form. If not removed within one year, additional letters were sent. Standardized IVC filter reporting templates were created and utilized after insertion of all filters with retrieval status. Letters were eventually built into the EMR for direct routing.RESULTS. From 2015 to 2020, IVC filters were placed in 719 patients. Of those, 58% were eligible for retrieval. Initial rates of rIVCF removal in eligible patients were as low as 30-33% in 2015. The retrieval rate of eligible filters rose to 44% in September 2018. The rate of retrieval rose to 61% in January 2021.CONCLUSIONS. Employing a systemic protocol to aid in follow-up of patients following rIVCF placement can improve rates of retrieval in the appropriate clinical setting. Regular evaluation and revision of the process played a significant role in achieving an increase in retrieval rates.